Moderate supercritical synthesis as a facile route to mixed-valent uranium(iv, v) and (v, vi) silicates. Issue 98 (24th October 2018) - Pace, Kristen A.; Klepov, Vladislav V.; Morrison, Gregory; zur Loye, Hans-Conrad
Abstract : The synthesis of five new U(iv, v ) and U(v, vi ) silicates points toward moderate supercritical synthesis as a new route to the stabilization of mixed-valent uranium compounds. Abstract : Mixed-valent uranium(iv, v ) and (v, vi ) phases represent a unique subset of known uranium compounds. Efforts to develop our current understanding of these materials have pointed to hydrothermal methods as effective preparative techniques. Herein we report the successful use of moderate supercritical conditions for the synthesis of five new U(v ) containing phases.